Legusa Festival: Membangun Jalan Humanitas Melalui Kreatifitas - Putra, Roni; Harun, Afrizal (Pascasarjana Institut Seni Indonesia Padang Panjang, 2024)
This research discusses the Legusa Festival as a means of building humanity through creativity in Nagari Tanjung Haro Sikabu-Kabu Padang Panjang. The main objective of this study is to explore the role of creativity as a path to humanity, which is the essence of human existence. The method used is action research, which involves planning, observation, and reflection to create a tangible social impact. The research results show that the Legusa Festival, with its various artistic and cultural activities, successfully connects the concept of creativity with humanity. This festival not only serves as a medium for artistic expression but also as a tool for producing and communicating local knowledge. The creativity generated by this festival is reflected in various art forms, ranging from music to film, involving collaboration between local artists and the community. The Legusa Festival also successfully creates an interactive space that brings together residents, thereby enhancing their ability to accept differences and build dialogue. Thus, this festival has become a means of humanization that promotes togetherness, understanding, and appreciation of cultural and social diversity.